SOSIALISASI PENGEMBANGAN KAWASAN EKOWISATA SEKITAR EKOSISTEM MANGROVE DI DESA WAIHERU KOTA AMBON - Tuhumena, Lolita; Maruanaya, Yan; Risakotta, Tesalonika K.; Demi, La; Tomasila, Leopold A (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
The good mangrove management for coastal communities in Ambon City, especially in Teluk Ambon Dalam (TAD) has many benefits. However, coastal communities which is living in mangrove ecosystem areas do not yet have much knowledge about the importance of mangroves and the benefits of the mangrove ecosystem. Therefore, the development of the Mitra/Innovation Village was carried out as an effort to contribute to the application of marine and fisheries science to build coastal villages in improving community welfare. The purpose of this Community Service (PKM) activity is to increase the knowledge and awareness of the Waiheru Village community about the importance of maintaining and preserving the mangrove ecosystem in a sustainable manner by maintaining environmental cleanliness in the context of developing ecotourism.The material presented in this socialization activity was about the function and benefits of the mangrove ecosystem in the development of Mangrove Ecotourism in Waiheru Village, Ambon City. After that, the Community Service (PKM) activity was continued by conducting a cleaning action around the mangrove ecosystem by cadets together with the village community. To determine the effectiveness of the Community Service (PKM) activity, the N-Gain Score approach was used with a value obtained of 67,86% (quite effective category). It is hoped that in the future the coastal community in Waiheru Village can increase efforts to preserve the mangrove ecosystem.